Apparent Sharpness of 3D Video When One Eye's View is More Blurry. (September 2013) - Robinson, Alan; Jain, Ankit; Scott, Mathew; MacLeod, Don; Nguyen, Truong
When the images presented to each eye differ in sharpness, the fused percept remains relatively sharp. Here, we measure this effect by showing stereoscopic videos that have been blurred for one eye, or both eyes, and psychophysically determining when they appear equally sharp. For a range of blur magnitudes, the fused percept always appeared significantly sharper than the blurrier view. From these data, we investigate to what extent discarding high spatial frequencies from just one eye's view reduces the bandwidth necessary to transmit perceptually sharp 3D content. We conclude that relatively high-resolution video transmission has the most potential benefit from this method.